Impact of urban aerosol properties on cloud condensation nuclei (CCN) activity during the KORUS-AQ field campaign. (July 2018) - Kim, Najin; Park, Minsu; Yum, Seong Soo; Park, Jong Sung; Shin, Hye Jung; Ahn, Joon Young
Abstract: Ground measurements of physical, chemical and hygroscopic properties of aerosols were made at the Olympic Park, Seoul, as part of the KORea-United States Air Quality study (KORUS-AQ) campaign in May–June 2016. The average number concentrations of aerosols larger than 10 nm in diameter and cloud condensation nuclei (CCN) at 0.6% supersaturation (S) were 10800 c m − 3 and 3400 c m − 3, respectively. The average geometric mean diameter ( D g ) was 44 nm, and size-resolved aerosol hygroscopicity (κ) from HTDMA ranged from 0.11 to 0.24 for particle diameters in the range of 30–150 nm. Aerosols were classified into three types based on mixing state and hygroscopic growth factor (GF): Type 1 (externally mixed aerosol), Type 2 (Internally mixed and growth aerosol) and Type 3 (internally mixed and non-growth aerosol). These three aerosol types showed distinct diurnal patterns. The difference in physical and chemical properties of aerosols for different air mass sources crucially impacted aerosol hygroscopicity. Using the external mixture assumption with measured hygroscopicity data improved the results of CCN prediction compared to those from the simple internal mixture assumption because externally mixed aerosols comprised a significant portion of aerosols in this urban area. Moreover, the simple assumption of aerosol size distribution with a fixed chemical composition sufficiently explained more than 50 percent of the variation of CCN number concentrations, although the information of chemical composition was still meaningful. Overall, the measured data showed consistency with Megacity Air Pollution Studies (MAPS-Seoul) campaign held during May–June 2015, implying that these results may represent urban aerosols in spring/summer in the Korean Peninsula. Highlight: Comprehensive aerosol measurement was made during the KORUS-AQ campaign. Aerosol hygroscopicity depended highly on aerosol physical and chemical properties. Mixing state and number size distribution are important for regulating CCN conc.